PENGARUH KETERLIBATAN KERJA DAN SPIRITUALITAS KERJA TERHADAP KOMITMEN ORGANISASI - Liwun, Stephanus Benedictus Bera (Universitas Gunadarma, 2016)
Employees in their work should have a commitment, but not only commitmentbut also the need to go beyond the assigned task. However in practice it is sometimesotherwise work is not considered a commitment by the company. This study aimedto examine the effect of job involvement to organizational commitment and toexamine the effect ofspirituality in the workplace to organizational commitment.The method used is quantitative method. This research use two independentvariables i.e. job involvement and spirituality ofwork, whereas one dependentvariable is organizational commitment. The results ofthis study isjob involvementto organizational commitment have an effect. Otherwise, the research is shownby the spirituality of work and organizational commitments have no effect.